(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The aim of this article is to present French gastronomy and its use in school education. This article presents the historical features of French cuisine, the composition of the French menu. Then we will cite some specificities of French cuisine in general. This article devotes to France’s own gastronomic division according to administrative division.